Road Damage Analysis using PCI and SDI Methods and Types Repair - Putri, Elsa Eka; Jamal, Riko; Yosritzal, Yosritzal (Universitas Negeri Padang, 2023)
The By-Pass Pariaman road section is a National Road under the authority of the West Sumatera National Road Implementation Agency with road section number N.048 with a length of 3.600 meters with the starting point of the “simp. IV Jati” and the ending point of the “simp. Apar”. In this study, an analysis of road damage conditions was carried out using PCI method and SDI method with the results: PCI method for the “simp. IV Jati – simp. Apar obtained that the most dominant percentage is good 40%, for the “simp. Apar – simp. IV Jati” the most dominant percentage is fair 36%. The SDI method for the “simp. IV Jati – simp. Apar” is good at 56%, medium at 30%, lightly damaged at 14% and heavily damaged at 0%, with a steady condition percentage of 86% and 14% unstable. The value of the road condition of the “simp. Apar – simp. IV Jati” is good at 47%, medium at 20%, lightly damaged at 33%, heavily damaged at 0%, with a steady condition percentage of 67% and unstable at 33%. For this type of road repair with PCI method for “simp. IV Jati – simp. Apar” is 2.200 meters of routine maintenance and 1.400 meters of periodic maintenance. The “simp. Apar – simp. IV Jati” can be routinely maintained for 2.000 meters and periodic maintenance for 1.600 meters. Road repairs with SDI method are generated for the “simp. IV Jati – simp. Apar” is 3.100 meters of routine maintenance and 500 meters of periodic maintenance. The “simp Apar – simp. IV Jati can be routinely maintained for 2.400 meters and regular maintenance for 1.200 meters.